If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1k = 36 Solving 5 + -1k = 36 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1k = 36 + -5 Combine like terms: 5 + -5 = 0 0 + -1k = 36 + -5 -1k = 36 + -5 Combine like terms: 36 + -5 = 31 -1k = 31 Divide each side by '-1'. k = -31 Simplifying k = -31
| 34=-17w | | 63=-3y | | 12(2+7)-24/12 | | 8x+1=7x-9 | | 6(4+x)=66 | | 6x-(3X-7)=29 | | 7x-(2x-22)=67 | | 4(x-5)=5(x-4)-x | | 6x1/2y=3 | | -4/3x+7/2=-3/4x-2 | | M=9n | | 2x/3-1=x-2/2 | | 5(2ab)= | | 5x^2-13-6=0 | | 2(5x+1)=92 | | 12-x=-16 | | 9x+11-2x=10-11x-12 | | (6+2)(28-27)= | | 5(-7x+5)=-10 | | -21/2*46/7 | | (6+2)(28-27)5= | | 4t-4=16-t | | -8-3x=22 | | (b+13)/2=-5b/3 | | s=180n-369 | | 37=-3-5(x+6) | | 3(1x-2)=-6 | | 1/5(85)=17 | | -1/6*-3/2 | | 37=-3-5(x-6) | | -14-2m=-2(5m-3) | | 6[1-(-3x-1)]=54x+24 |